Vivian L. answered • 02/09/14

Microsoft Word/Excel/Outlook, essay composition, math; I LOVE TO TEACH

Hi Roseland;

x

^{2}+6x+9=36x

^{2}+6x+9 can be factored as (x+3)^{2}=(x+3)(x+3)...Let's FOIL this...

FIRST...(x)(x)=x

^{2}OUTER...(x)(3)=3x

INNER...(3)(x)=3x

LAST...(3)(3)=9

x

^{2}+3x+3x+9x

^{2}+6x+9(x+3)

^{2}=36Let's take the square root of both sides...

√[(x+3)

^{2}=√36+/-(x+3)=6

Please remember that if you square a number you produce the same result as its negative counterpart squared.

x+3=6, x=3

-(x+3)=6, -x-3=6, -x=9, x=-9